Exploring Reduplication as A Morphological Process in Balinese Folktales - A. A. Pt., Suari (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2025)
This study examines reduplication patterns in Balinese using a corpus-based approach, highlighting the language’s rich and complex morphology. The data source is Kumpulan Satua (Balinese Folktales) by Suwija, Darmada, and Mulyawan (2019), consisting of 62 narrative texts converted into plain text and processed with AntConc 3.5.8. Reduplicated forms were identified with Regular Expressions (Regex), yielding 142 valid instances after filtering and verification. Analysis combined quantitative frequency counts with qualitative classification based on Carstairs-McCarthy (2002) and Sneddon (2020). Results show that partial reduplication (40.78%) and full reduplication (39.47%) dominate, confirming their central role in lexical formation and semantic extension. Other types—Ca-reduplication (13.82%), vowel alternation (12.50%), and echo-words (6.58%)—further illustrate the language’s phonological and semantic creativity. The identification of Ca-reduplication as a productive process contributes new insights to Balinese linguistics. Overall, the study advances understanding of Balinese morpho-semantics while offering implications for grammar teaching, language preservation, and curriculum design.